2020
DOI: 10.1155/2020/7804706
|View full text |Cite
|
Sign up to set email alerts
|

EEF1D Promotes Glioma Proliferation, Migration, and Invasion through EMT and PI3K/Akt Pathway

Abstract: Eukaryotic translation elongation factor 1δ (EEF1D), a subunit of the elongation factor 1 complex of proteins, mediates the elongation process of protein synthesis. Besides this canonical role, EEF1D was found overexpressed in many tumors, like hepatocarcinomas and medulloblastomas. In the present study, we demonstrated for the first time that EEF1D may interact with other putative proteins to regulate cell proliferation, migration, and invasion through PI3K/Akt and EMT pathways in glioma. Furthermore, knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…In a study of gliomas, it was found that after knocking out EEF1D in glioma cells, the expression of mesenchymal markers including N-cadherin and snail was significantly down-regulated. In addition, β-catenin, a key transcription factor in the EMT process, was also reduced (32). These findings indicate that EEF1D is closely related to the regulation of the EMT process in glioma cells.…”
Section: The Role Of Eef1d In Tumor Invasionmentioning
confidence: 67%
See 2 more Smart Citations
“…In a study of gliomas, it was found that after knocking out EEF1D in glioma cells, the expression of mesenchymal markers including N-cadherin and snail was significantly down-regulated. In addition, β-catenin, a key transcription factor in the EMT process, was also reduced (32). These findings indicate that EEF1D is closely related to the regulation of the EMT process in glioma cells.…”
Section: The Role Of Eef1d In Tumor Invasionmentioning
confidence: 67%
“…These findings indicate that EEF1D may enhance the Akt-mTOR and Akt-Bad signaling pathways, and plays an important role in the growth of osteosarcoma cells (31). In gliomas, it has also been found that the down-regulation of EEF1D expression can inhibit the activation of the PI3K/Akt pathway and hinder cell proliferation (32).…”
Section: Eef1d Regulates Tumor Cell Proliferation and Tumor Growthmentioning
confidence: 80%
See 1 more Smart Citation
“…These proteins can promote the PI3K pathway. [24][25][26] Additionally, microarray data showed an increase in Akt expression with GV1001 treatment. After activation, NSCs differentiate into neural cells that replace damaged cells during neurogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Among these targets, eukaryotic translation elongation factor 1 delta (EEF1D) has been reported to modulate proliferation and epithelial-mesenchymal transition in oral squamous cell carcinoma [ 30 ] and promote glioma proliferation, migration, and invasion through epithelial-mesenchymal transition and PI3K/Akt pathway [ 31 ]. For eukaryotic translation initiation factor 3, subunit B (EIF3B) expression was found to be upregulated in gastric cancer tissues; it is strongly associated with proliferating cell nuclear antigen (PCNA) expression and is associated with poor outcomes in gastric cancer patients [ 32 ].…”
Section: Resultsmentioning
confidence: 99%